The State of Remote Patient Monitoring for Chronic Disease Management in the United States - Margaret M Paul; Nandita Khera; Praneetha R Elugunti; Kevin C Ruff; Musab S Hommos; Leslie F Thomas; Vivek Nagaraja; Ashley L Garrett; Mari Pantoja-Smith; Nathan L Delafield; Blanca C Lizaola-Mayo; Molly M Kresin; et al. (Journal of Medical Internet Research)
Remote patient monitoring (RPM) increased exponentially during the COVID-19 pandemic. RPM programs commonly incorporate tools to capture and transmit health-relevant data from the home to the clinical space to augment the clinical decision-making process of health care providers. Given the potential to improve patient health outcomes, health care systems around the world are actively engaged in fashioning, implementing, and exploring the outcomes of various RPM program models. However, new challenges to health care systems include increasing RPM program enrollment, optimizing condition-specific RPM programs to best address the needs of specific patient groups, integrating new RPM-derived data streams into existing IT infrastructure, overcoming limited availability of desired remote monitoring technologies, and quantifying the health outcomes produced by RPM use. Herein, we identify stakeholders for RPM in the United States, summarize the landscape of RPM tools available for chronic disease management, discuss the current regulatory environment, delve into the benefits and challenges of integrating these tools into clinical practice, summarize aspects of coverage and reimbursement, and examine the knowledge and policy gaps regarding sustained use of RPM in clinical practice, along with associated opportunities.